PEDAGOGICAL METHODS BEHIND TEACHING THE PRACTITIONER-PATIENT INTERVIEW IN FRENCH - Ariel-Sebastián Mercado (Journal of Languages for Specific Purposes, 2024)
The practitioner-patient interview has been the subject of several studies in the world of medicine and in the field of teaching languages for specific purposes It has been considered one of the most critical oral genres in language teaching for medical-health purposes. Every health professional has to know and understand why the patient has come for a consultation; they must have the necessary skills to obtain as much information about the patient’s health problem as possible, and if necessary, they have to perform a physical examination. The practitioner-patient interview is divided into several steps. Each step consists of a specific task with its specific objectives for the practitioner. For about fifteen years, the French Language Centre of McGill University, an English-speaking university in Montreal, Canada, has been offering French courses to students specializing in different areas of the Faculty of Health Sciences and Social Work who wish to do their clinical placements and pursue their professional career in the province of Quebec. Most of McGill’s students are native English speakers from different parts of Canada and the United States or international students whose first language is not necessarily English. One of the most important oral genres which must be taught to these students is the practitioner-patient interview in French, since one of their principal tasks as healthcare professionals will to interact with patients. Furthermore, students who have obtained a degree in any healthcare profession from an English-speaking university in the French-speaking province of Quebec must take a French language exam offered by the Office québécois de la langue française (OQLF). In one of the activities of this exam, the candidates must interview a patient or a caregiver in French. Therefore, this constitutes another reason to teach the practitioner-patient interview to our students. Unfortunately, there is little extant literature on how to teach students to carry out a practitioner-patient interview in French as a second language. Moreover, the possibility of recording actual interviews for use in class is practically impossible to respect patient confidentiality. This paper aims to share with the scientific community and with other language for specific purposes instructors how the practitioner-patient interview is taught at McGill University to non-native French speakers who wish to work in Quebec.